National survey of the prevalence, incidence, primary care burden, and treatment of heart failure in Scotland. Issue 10 (14th September 2004) - Murphy, N F; Simpson, C R; McAlister, F A; Stewart, S; MacIntyre, K; Kirkpatrick, M; Chalmers, J; Redpath, A; Capewell, S; McMurray, J J V
Abstract : Objective: To examine the epidemiology, primary care burden, and treatment of heart failure in Scotland, UK. Design: Cross sectional data from primary care practices participating in the Scottish continuous morbidity recording scheme between 1 April 1999 and 31 March 2000. Setting: 53 primary care practices (307 741 patients). Subjects: 2186 adult patients with heart failure. Results: The prevalence of heart failure in Scotland was 7.1 in 1000, increasing with age to 90.1 in 1000 among patients ⩾ 85 years. The incidence of heart failure was 2.0 in 1000, increasing with age to 22.4 in 1000 among patients ⩾ 85 years. For older patients, consultation rates for heart failure equalled or exceeded those for angina and hypertension. Respiratory tract infection was the most common co-morbidity leading to consultation. Among men, 23% were prescribed a β blocker, 11% spironolactone, and 46% an angiotensin converting enzyme inhibitor. The corresponding figures for women were 20% (p  =  0.29 versus men), 7% (p  =  0.02), and 34% (p < 0.001). Among patients < 75 years 26% were prescribed a β blocker, 11% spironolactone, and 50% an angiotensin converting enzyme inhibitor. The corresponding figures for patients ⩾ 75 years were 19% (p  =  0.04 versus patients < 75), 7% (p  =  0.04), and 33% (p < 0.001). Conclusions: Heart failure is a common condition, especially with advancing age. In the elderly, the community burden of heart failure is at least as great as that of angina or hypertension. The high rate of concomitant respiratory tract infection emphasises the need for strategies to immunise patients with heart failure against influenza and pneumococcal infection. Drugs proven to improve survival in heart failure are used less frequently for elderly patients and women.